EQUITABLE ACCESS - Manica Balasegaram; Jennifer Cohn (International Journal of Infectious Diseases, 2023)
The COVID-19 epidemic has once again highlighted the challenges to achieve equitable access to critical antimicrobials and vaccines. The problem is particularly acute for antimicrobials.Despite recent investments improving the pipeline for new treatments, most new treatments are not available to populations most in need, especially in low- and middle-income countries. Once a drug is approved a range of factors may hinder access, from lack incentives to register and commercialize products due to unattractive market potential to unfunded national action plans that can help improve the uptake and appropriate use of new tools to combat antibiotic resistance. Previous studies have shown that the majority of the 18 new antibacterials approved and launched between 2010-2020 were accessible in only 3 out of 14 high-income countries (Sweden, UK, and US). In low- and middle-income countries, the problem is even worse, with only 10 of the 25 new antibiotics that entered the market between 1999 and 2014 registered in more than ten countries.While lack of equitable access to life-saving medicines, diagnostics, and vaccines is not a new problem for infectious diseases, emerging opportunities and innovative approaches can help improve access globally. This talk will review promising recent developments in governance and collaborations, policies, economic models and initiatives that may help correct deadly inequities.For example, the objectives of the Access to COVID-19 Tools Accelerator may serve as model that convenes diverse actors to mount a coordinated access response which may be applied to access to other antimicrobials and vaccines. In addition, novel licensing agreements for access and stewardship to cefiderocol, an antimicrobial that is on the WHO Essential Medicines List can help serve as a pathfinder to accelerate equitable access to novel antimicrobials. The talk will also surface critiques of ongoing initiatives and raise questions for further study and discussion.